Dupilumab reduces systemic corticosteroid use and sinonasal surgery rate in CRSwNP - Desrosiers, M; Mannent, L P; Amin, N; Canonica, G W; Hellings, P W; Gevaert, P; Mullol, J; Lee, S E; Fujieda, S; Han, J K; Hopkins, C; Fokkens, W; et al. (Rhinology, 2021)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a type 2 inflammatory disease with a high symptom burden and poor quality of life. Treatment options include recurrent surgeries and/or frequent systemic corticosteroids (SCS). Dupilumab, a fully human monoclonal antibody, blocks the shared receptor component for interleukin-4 and interleukin-13, key drivers of type 2-mediated inflammation. We report results of pooled analyses from 2 randomised, double-blind, placebo-controlled phase 3 studies (SINUS 24 [NCT02912468]; SINUS-52 [NCT02898454]) to evaluate dupilumab effect versus placebo in adults with CRSwNP with/without SCS use and sinonasal surgery. SINUS-24 patients were randomised 1:1 to subcutaneous dupilumab 300 mg (n=143) or placebo (n=133) every 2 weeks (q2w) for 24 weeks. SINUS-52 patients were randomised 1:1:1 to 52 weeks of subcutaneous dupilumab 300 mg q2w (n=150), 24 weeks q2w followed by 28 weeks of dupilumab 300 mg every 4 weeks (n=145) or 52 weeks of placebo q2w (n=153). Dupilumab reduced the number of patients undergoing sinonasal surgery (82.6%), the need for in-study SCS use (73.9%), and SCS courses (75.3%). Significant improvements were observed with dupilumab vs placebo regardless of prior sinonasal surgery or SCS use in nasal polyp, nasal congestion, Lund-MacKay, and Sinonasal Outcome Test (22-items) scores, and the University of Pennsylvania Smell Identification Test. Dupilumab demonstrated significant improvements in disease signs and symptoms and reduced the need for sino-nasal surgery and SCS use versus placebo in patients with severe CRSwNP, regardless of SCS use in the previous 2 years, or prior sinonasal surgery.